1998
DOI: 10.1002/lt.500040112
|View full text |Cite
|
Sign up to set email alerts
|

Torulopsis glabrata fungemia as a complication of a clotted transjugular intrahepatic portosystemic shunt

Abstract: Torulopsis glabrata fungemia developed in a patient with a clotted transjugular intrahepatic portosystemic shunt (TIPS) 11 months after placement. Fungemia persisted despite treatment with amphotericin B. On autopsy, T. glabrata was found in the thrombus occluding the TIPS and extending into the splenic and portal vein. TIPS infections may be considered in patients with fungemia. Copyright 1998 by the American Association for the Study of Liver Diseases T orulopsis glabrata (Candida glabrata) is considered to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The term ''definite endotipsitis'' was coined for continuous bacteremia with an observed vegetation or thrombus in the TIPS stent, while ''probable endotipsitis'' refers to persistent bacteremia and fever with an apparently normal stent and no other obvious source of infection. 53,54 A variety of organisms have been isolated from such cases, including gram-negative enteric pathogens, Staphylococcus aureus, and enterococci and also fungal TIPS stent infections, [55][56][57] the latter as all other infections potentially lethal with sepsis and multiorgan failure. There were no special reports on increased incidence of endotipsitis after VIATORR 1 endoprosthesis placement.…”
Section: Concerns and Complicationsmentioning
confidence: 99%
“…The term ''definite endotipsitis'' was coined for continuous bacteremia with an observed vegetation or thrombus in the TIPS stent, while ''probable endotipsitis'' refers to persistent bacteremia and fever with an apparently normal stent and no other obvious source of infection. 53,54 A variety of organisms have been isolated from such cases, including gram-negative enteric pathogens, Staphylococcus aureus, and enterococci and also fungal TIPS stent infections, [55][56][57] the latter as all other infections potentially lethal with sepsis and multiorgan failure. There were no special reports on increased incidence of endotipsitis after VIATORR 1 endoprosthesis placement.…”
Section: Concerns and Complicationsmentioning
confidence: 99%
“…Notably, Candida infections , as compared to bacterial infections, have been associated with the highest mortality (>60%) . Only four prior cases of Candida ‐associated endotipsitis have been documented in the literature, of which only one responded to antifungal treatment (Table ) . While the role of prophylactic antibiotics has been studied in post‐TIPS patients, no study has yet to evaluate prophylactic antifungal therapy in post‐operative TIPS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most reported TIPS infections have been attributed to enteric bacteria [5,7 Á9]; however, three cases of TIPS infection caused by Candida species have been reported [5,6,10]. Two fatal cases involved Candida glabrata fungemia that was unsuccessfully managed with fluconazole/5-flucytosine and amphotericin B treatment regimens.…”
Section: Introductionmentioning
confidence: 98%
“…Two fatal cases involved Candida glabrata fungemia that was unsuccessfully managed with fluconazole/5-flucytosine and amphotericin B treatment regimens. Autopsies revealed that the TIPS were occluded with organized thrombi containing numerous yeast organisms [6,10]. A third case involved a patient with a thrombotic TIPS who was infected with fluconazole-sensitive Candida albicans [5].…”
Section: Introductionmentioning
confidence: 99%